Dari Ritual dan Liturgi: Mengintegrasikan Nilai- Nilai Budaya Irau Ke Dalam Pelayanan Gerejawi di Paroki St. Stefanus Malinau - Marini, Marini; Intansakti Pius X; Emmeria Tarihoran (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This study examines the integration of Irau cultural values into Catholic Church ministry in Malinau through the approach of inculturation. The Irau festival, as a cultural heritage of the Dayak community, contains social and spiritual values such as togetherness, brotherhood, and gratitude. The study employs a qualitative method with a library research approach, analyzing Catholic Church documents, literature on inculturation theology, anthropiological studies on Dayak culture, and publications related to Malinau. The results indicate that integrating Irau cultural elements, such as music, dance, and traditional symbols that align with Catholic teaching, can enrich liturgy and pastoral ministry. This inculturation helps Catholics experience their faith contextually while respecting their cultural identity. A selective process is necessary to purify cultural elements that conflict with faith, enabling the Church to be an integral part of Malinau society.